# calculus

express in sinx
1 1
---------- + --------
cscx + cotx cscx - cotx

and express in cosx

1 + cot x
------- - sin^2x

cscx = 1/sinx so what do i do w. that extra one on the top!?? im so confused
cscx

Your fractions aren't lining up. This question is also not calculus. Please do not post with different names.

1. 👍 0
2. 👎 0
3. 👁 152

## Similar Questions

1. ### trig

express this in sinx (1/ cscx + cotx )+ (1/cscx- cotx) i got 2sinx is that right?? and B) express in cosx problem: is 1 + cotx/cscx - sin^2x i get to the step of 1 + cos-sin^2x and im stuck..help! (1/cscx + cotx) + (1/cscx - cotx)

asked by linds on March 28, 2007
2. ### drwls

My previous question: Verify that (secx/sinx)*(cotx/cscx)=cscx is an identity. (secx/sinx)*(cotx/cscx) = (secx/cscx)(cotx/sinx) = (sinx/cosx)*cotx*(1/sinx) "The last steps should be obvious" Not to me. I can convert (sinx/cosx) to

asked by Jon on March 7, 2008
3. ### Pre-Calculus

Find a numerical value of one trigonometric function of x if tanx/cotx - secx/cosx = 2/cscx a) cscx=1 b) sinx=-1/2 c)cscx=-1 d)sinx=1/2

asked by Lucy on August 30, 2008
4. ### Calculus

Prove the identity cscx+cotx-1/cotx-cscx+1 = 1+cosx/sinx

asked by Anonymous on October 15, 2018
5. ### ap calc bc

hi! ok, i know that deriv(cscx) = -cscxcotx and that deriv(cos) = -sinx deriv(cotx) = -((cscx)^2) my question is: is this (statements below) correct? antideriv(cscxcotx) = -(cscx) antideriv(sinx) = -cosx antideriv((cscx)^2)= -cotx

asked by APpreciate student on October 27, 2010
6. ### Trig

Verify that (secx/sinx)*(cotx/cscx)=cscx is an identity. (x=theta BTW)

asked by Jon on March 7, 2008
7. ### Precalculus/Trig

I can't seem to prove these trig identities and would really appreciate help: 1. cosx + 1/sin^3x = cscx/1 - cosx I changed the 1: cosx/sin^3x + sin^3x/sin^3x = cscx/1-cosx Simplified: cosx + sin^3x/sin^3x = cscx/1-cosx I don't

asked by Heather on August 15, 2014
8. ### Math

Im really struggling with these proving identities problems can somebody please show me how to do these? I'm only aloud to manipulate one side of the equation and it has to equal the other side of the equation at the end Problem

asked by Alycia on November 1, 2012
9. ### AP calculus BC

hello i know that deriv(cscx) = -cscxcotx and that deriv(cos) = -sinx deriv(cotx) = -((cscx)^2) my question is: is this (statements below) correct? antideriv(cscxcotx) = -(cscx) antideriv(sinx) = -cosx antideriv((cscx)^2)= -cotx

asked by CALLIE CALC on October 27, 2010
10. ### Math

Verify the identity . (cscX-cotX)^2=1-cosX/1+cosX _______ sorry i cant help you (cscX-cotX)=1/sinX - cosX/sinX = (1-cosX)/sinX If you square this you have (1-cosX)^2/(sinX)^2 Now use (sinX)^2 = 1 - (cosX)^2 to get (1-cosX)^2 / 1 -

asked by Rose on October 9, 2006

More Similar Questions